Thickness estimation of supraglacial debris above ice cliff exposures using a high-resolution digital surface model derived from terrestrial photography - L. NICHOLSON; J. MERTES (Journal of Glaciology, 2017)
The thickness of supraglacial debris cover controls how it impacts the ablation rate of underlying glacier ice, yet this quantity remains challenging to measure, particularly at glacier scales. We present a relatively straightforward, and cost-effective method to estimate debris thickness exposed above ice cliffs using simplified geometrical measurements from a high-resolution digital surface model (DSM), derived from a terrestrial photographic survey and a Structure from Motion with Multi-View Stereo workflow (SfM-MVS). As the ice surface relief beneath the debris cover is unknown, we assume it to be horizontal and provide error bounds based on characteristic ice-surface slope at the visible debris/ice interface. Debris thickness around the three sampled ice cliffs was highly variable (interquartile range of 0.80–2.85 m) and negatively skewed with a mean thickness of 2.08 ± 0.68 m. Manual, and high-frequency radar, determinations of debris thickness in the same area show similar thickness distributions, but statistically different mean debris thickness, due to local heterogeneity. Debris thickness values derived in this study all exceed estimates from satellite surface temperature inversions. Wider application of the method presented here would provide useful data for improving debris thickness approximations from satellite imagery.